A clinical tool to calculate post‐transplant survival using pre‐transplant clinical characteristics in adults with cystic fibrosis. Issue 6 (23rd April 2017) - Stephenson, Anne L.; Sykes, Jenna; Berthiaume, Yves; Singer, Lianne G.; Chaparro, Cecilia; Aaron, Shawn D.; Whitmore, George Alex; Stanojevic, Sanja
Abstract: Background: We previously identified factors associated with a greater risk of death post‐transplant. The purpose of this study was to develop a clinical tool to estimate the risk of death after transplant based on pre‐transplant variables. Methods: We utilized the Canadian CF registry to develop a nomogram that incorporates pre‐transplant clinical measures to assess post‐lung transplant survival. The 1‐, 3‐, and 5‐year survival estimates were calculated using Cox proportional hazards models. Results: Between 1988 and 2012, 539 adult Canadians with CF received a lung transplant with 208 deaths in the study period. Four pre‐transplant factors most predictive of poor post‐transplant survival were older age at transplantation, infection with B. cepacia complex, low FEV1 percent predicted, and pancreatic sufficiency. A nonlinear relationship was found between risk of death and FEV1 percent predicted, age at transplant, and BMI. We constructed a risk calculator based on our model to estimate the 1‐, 3‐, and 5‐year probability of survival after transplant which is available online. Conclusions: Our risk calculator quantifies the risk of death associated with lung transplant using pre‐transplant factors. This tool could aid clinicians and patients in the decision‐making process and provide information regarding the timing of lung transplantation.